Genetic polymorphisms in the circumsporozoite protein of Plasmodium malariae show a geographical bias - Saralamba, N; Mayxay, M; Newton, P; Smithuis, F; Nosten, F; Archasuksan, L; Pukrittayakamee, S; White, N; Day, N; Dondorp, A; Imwong, M (BioMed Central, 2018)
Background Plasmodium malariae is characterized by its long asymptomatic persistence in the human host. The epidemiology of P. malariae is incompletely understood and is hampered by the limited knowledge of genetic polymorphisms. Previous reports from Africa have shown heterogeneity within the P. malariae circumsporozoite protein (pmcsp) gene. However, comparative studies from Asian countries are lacking. Here, the genetic polymorphisms in pmcsp of Asian isolates have been characterized. Methods Blood samples from 89 symptomatic P. malariae-infected patients were collected, from Thailand (n = 43), Myanmar (n = 40), Lao PDR (n = 5), and Bangladesh (n = 1). pmcsp was amplified using semi-nested PCR before sequencing. The resulting 89 pmcsp sequences were analysed together with 58 previously published pmcsp sequences representing African countries using BioEdit, MEGA6, and DnaSP. Results Polymorphisms identified in pmcsp were grouped into 3 populations: Thailand, Myanmar, and Kenya. The nucleotide diversity and the ratio of nonsynonymous to synonymous substitutions (dN/dS) in Thailand and Myanmar were higher compared with that in Kenya. Phylogenetic analysis showed clustering of pmcsp sequences according to the origin of isolates (Asia vs. Africa). High genetic differentiation (Fst = 0.404) was observed between P. malariae isolates from Asian and African countries. Sequence analysis of pmcsp showed the presence of tetrapeptide repeat units of NAAG, NDAG, and NAPG in the central repeat region of the gene. Plasmodium malariae isolates from Asian countries carried fewer copies of NAAG compared with that from African countries. The NAPG repeat was only observed in Asian isolates. Additional analysis of 2 T-cell epitopes, Th2R and Th3R, showed limited heterogeneity in P. malariae populations. Conclusions This study provides valuable information on the genetic polymorphisms in pmcsp isolates from Asia and advances our understanding of P. malariae population in Asia and Africa. Polymorphisms in the central repeat region of pmcsp showed association with the geographical origin of P. malariae isolates and can be potentially used as a marker for genetic epidemiology of P. malariae population.